Sequence stratigraphy and relative sea level variations in Kaštela Bay, Dalmatian coast, Croatia, and implications for the submerged palaeolandscapes and archaeology of the late Pleistocene, marine isotope stage 3 and marine isotope stage 2 - Simon Fitch; Slavica Bosnjak; Jessica W. Cook Hale; Vedran Barbarić; Timothy A. Shaw; Tanghua Li (Quaternary Science Reviews, 2025)

Late-Holocene sea-level markers preserved in a beach ridge system on Phra Thong Island, Thailand - Rahul Kumar; Adam D. Switzer; Chris Gouramanis; Charles S. Bristow; Timothy A. Shaw; Kruawun Jankaew; Tanghua Li; Dominik Brill (Geomorphology, 2024)

The preservation of storm events in the geologic record of New Jersey, USA - Kristen M. Joyse; Jennifer S. Walker; Linda Godfrey; Margaret A. Christie; Timothy A. Shaw; D. Reide Corbett; Robert E. Kopp; Benjamin P. Horton (Journal of Quaternary Science, 2024)
Geologic reconstructions of overwash events can extend storm records beyond the brief instrumental record. However, the return periods of storms calculated from geologic records alone may underestimate the frequency of events given the preservation bias of geologic records. Here, we compare a geologic reconstruction of storm activity from a salt marsh in New Jersey to two neighboring instrumental records at the Sandy Hook and Battery tide gauges. Eight overwash deposits were identified within the marsh's stratigraphy by their fan‐shaped morphology and coarser mean grain size (3.6 ± 0.7 φ) compared to autochthonous sediments they were embedded in (5.6 ± 0.8 φ). We used an age–depth model based on modern chronohorizons and three radiocarbon dates to provide age constraints for the overwash deposits. Seven of the overwash deposits were attributed to historical storms, including the youngest overwash deposit from Hurricane Sandy in 2012. The four youngest overwash deposits overlap with instrumental records. In contrast, the Sandy Hook and Battery tide gauges recorded eight and 11 extreme water levels above the 10% annual expected probability (AEP) of exceedance level, respectively, between 1932/1920 and the present. The geologic record in northern New Jersey, therefore, has a 36–50% preservation potential of capturing extreme water levels above the 10% AEP level.

Glacial Isostatic Adjustment modelling of the mid-Holocene sea-level highstand of Singapore and Southeast Asia - Tanghua Li; Stephen Chua; Fangyi Tan; Nicole S. Khan; Timothy A. Shaw; Jedrzej Majewski; Aron J. Meltzner; Adam D. Switzer; Patrick Wu; Benjamin P. Horton (Quaternary Science Reviews, 2023)

Seasonal Rainfall, Shrub Cover and Soil Properties Drive Production of Winter Annuals in the Northern Sonoran Desert - Julea A. Shaw; Scott L. Collins; Timothy J. Ohlert; Hannah Heavenrich; Elizabeth Cook; Megan M. Wheeler; Nancy B. Grimm; Sharon J. Hall (Ecosystems, 2023)

Coastal response to global warming during the Paleocene-Eocene Thermal Maximum - Glenn R. Sharman; Jacob A. Covault; Peter P. Flaig; Regan Dunn; Preston Fussee-Durham; Toti E. Larson; Timothy M. Shanahan; Kalli Dubois; John B. Shaw; James L. Crowley; Barry Shaulis (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Distribution and stability of Mn complexes in the ocean: Influence of hydrothermal plumes and weather events - Aubin Thibault de Chanvalon; George W. Luther; Véronique E. Oldham; Bradley M. Tebo; Nicole R. Coffey; Timothy F. Shaw (Limnology and Oceanography, 2023)
We measured the speciation of dissolved Mn from the surface to just above the hydrothermal vents at 9°50′N East Pacific Rise in the open ocean of the Pacific over a 3‐week period. Total dissolved Mn concentrations ranged from 2.2 to 135 nmol L −1 with a significant contribution of dissolved Mn(III) bound to humic acid in one third of our samples representing up to 64% of the total dissolved Mn. These humic complexes were mostly detected in the hydrothermal vent plume and at the redox boundaries of the oxygen minimum zone in the water column. In the hydrothermal plume, the Mn(III)‐humic acid stabilized the manganese in solution up to a ~ 10,000‐fold dilution of the venting water. In the upper water column, Mn(III)‐humic acid was only detected after a squall and rain event, which indicates that it is a transient species, persistent over days to weeks. This temporal variability highlights the importance of non‐steady‐state processes in the open ocean, which may help to explain previous observations of a dissolved Mn maximum within oceanic oxygen minimum zones.

An interaction of inorganic arsenic exposure with body weight and composition on type 2 diabetes indicators in Diversity Outbred mice - James G. Xenakis; Christelle Douillet; Timothy A. Bell; Pablo Hock; Joseph Farrington; Tianyi Liu; Caroline E. Y. Murphy; Avani Saraswatula; Ginger D. Shaw; Gustavo Nativio; Qing Shi; Abhishek Venkatratnam; et al. (Mammalian Genome, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Transcranial Doppler sonography reveals sustained attention deficits in young adults diagnosed with ADHD - Tyler H. Shaw; Timothy W. Curby; Kelly Satterfield; Samuel S. Monfort; Raul Ramirez (Experimental Brain Research, 2019)

The use of high-throughput sequencing to investigate an outbreak of glycopeptide-resistant Enterococcus faecium with a novel quinupristin-dalfopristin resistance mechanism - Timothy D. Shaw; D. J. Fairley; T. Schneiders; M. Pathiraja; R. L. R. Hill; G. Werner; J. S. Elborn; R. McMullan (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

New Approaches to Continuing Medical Education: a QStream (spaced education) Program for Research Translation in Ovarian Cancer - Tracy Robinson; Anna Janssen; Judy Kirk; Anna DeFazio; Annabel Goodwin; Kathy Tucker; Timothy Shaw (Journal of Cancer Education, 2017)

Hydrous Ferric Oxides in Sediment Catalyze Formation of Reactive Oxygen Species during Sulfide Oxidation - Sarah A. Murphy; Shengnan Meng; Benson M. Solomon; Dewamunnage M. C. Dias; Timothy J. Shaw; John L. Ferry (Frontiers in Marine Science, 2016)

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins - Przemyslaw Szafranski; Tomasz Gambin; Avinash V. Dharmadhikari; Kadir Caner Akdemir; Shalini N. Jhangiani; Jennifer Schuette; Nihal Godiwala; Svetlana A. Yatsenko; Jessica Sebastian; Suneeta Madan-Khetarpal; Urvashi Surti; Rosanna G. Abellar; et al. (Human Genetics, 2016)

Examining why trends in very heavy precipitation should not be mistaken for trends in very high river discharge - Timothy J. Ivancic; Stephen B. Shaw (Climatic Change, 2015)

Holocene Relative Sea-Level Changes from Near-, Intermediate-, and Far-Field Locations - Nicole S. Khan; Erica Ashe; Timothy A. Shaw; Matteo Vacchi; Jennifer Walker; W.R. Peltier; Robert E. Kopp; Benjamin P. Horton (Current Climate Change Reports, 2015)

Resource distribution drives the adoption of migratory, partially migratory, or residential strategies - Timothy C. Reluga; Allison K. Shaw (Theoretical Ecology, 2015)

Islands of Ice: Influence of Free-Drifting Antarctic Icebergs on Pelagic Marine Ecosystems - Maria Vernet; Kenneth Smith; Adrián Cefarelli; John Helly; Ronald Kaufmann; Hai Lin; David Long; Alison Murray; Bruce Robison; Henry Ruhl; Timothy Shaw; Alana Sherman; et al. (Oceanography, 2012)

Dietary exposure to titanium dioxide nanoparticles in rainbow trout, (Oncorhynchus mykiss): no effect on growth, but subtle biochemical disturbances in the brain - Christopher S. Ramsden; Timothy J. Smith; Benjamin J. Shaw; Richard D. Handy (Ecotoxicology, 2009)

Genetic analysis of avian influenza A viruses isolated from domestic waterfowl in live-bird markets of Hanoi, Vietnam, preceding fatal H5N1 human infections in 2004 - Samadhan J. Jadhao; Doan C. Nguyen; Timothy M. Uyeki; Michael Shaw; Taronna Maines; Thomas Rowe; Catherine Smith; Lien P. T. Huynh; Ha K. Nghiem; Diep H. T. Nguyen; Hang K. L. Nguyen; Hanh H. T. Nguyen; et al. (Archives of Virology, 2009)

BOOK REVIEW | Chemical Oceanography and the Marine Carbon Cycle - Timothy Shaw (Oceanography, 2009)

The new hominid skeleton from Sterkfontein, South Africa: age and preliminary assessment - Timothy C. Partridge; John Shaw; David Heslop; Ronald J. Clarke (Journal of Quaternary Science, 1999)